Thermomagnetic analysis applied for identification of lithogenic and pedogenic iron oxides in topsoils from Bulgaria - Neli Jordanova; Diana Jordanova (GeoStudies, 2024)
Identification of magnetic minerals, which determine the magnetic properties of natural rocks, sediments and soils, is of crucial importance for any further interpretation of their magnetic signature in environmental or paleogeographical context. One of the major and widely used methods for determination of kind of magnetic phases in natural materials is by obtaining the Curie/Neel temperature of the respective magnetic mineral. In this contribution, we report a set of thermomagnetic measurements of high-temperature behavior of magnetic susceptibility for topsoils from the territory of Bulgaria, aiming to reveal the pedogenic and lithogenic signature. The data are considered and reported in respect to the parent rock type. Our results suggest that pedogenic magnetic minerals are represented mainly by fine-grained maghemite and/or hematite with possible Al-substitutions in the crystal lattice. This phase is expressed on the heating run of the thermomagnetic curve as a “hump” with a maximum at 250–300 °C. Coarse-grained magnetite is identified as a dominant lithogenic magnetic mineral. Hematite’s presence in a sub-set of red-colored soils is confirmed by additional analyses of isothermal remanence acquisition curves. Two hematite coercivity components were identified, related to pedogenic and lithogenic origin, respectively.